Worse than Baumol's disease: The implications of labor productivity, contracting out, and unionization on transit operation costs. (January 2018) - Morales Sarriera, Javier; Salvucci, Frederick P.; Zhao, Jinhua
Abstract: Unit costs measured as bus operating costs per vehicle mile have increased considerably above the inflation rate in recent decades in most transit agencies in the United States. This paper examines the impact of (lack of) productivity growth, union bargaining power, and contracting out on cost escalation. We draw from a 17-year (1997–2014) and a 415-bus transit agency panel with 5780 observations by type of operation (directly operated by the agency or contracted out). We have three main findings: first, the unit cost increase in the transit sector is far worse than what economic theory predicts for industries with low productivity growth. Second, contracting out tends to reduce unit costs, and the results suggest that the costs savings from private operations can be only partly explained by lower wages in the private sector. Interestingly, we find that the cost savings from contracting out are larger when the transit agency also directly operates part of the total transit service. However, while overall unit costs are lower in contracted services, cost growth in large private bus operators is no different than cost growth in large public transit operators. Third, unique transit labor laws that lead to union bargaining power are a likely driver of the unit cost growth above inflation. Overall, these factors reflect inherent characteristics of the bus transit sector, such as the nature of low productivity growth and union legislative power related to the need for public subsidy. They drive increases in both transit fares and public subsidy at rates higher than inflation, and play an important role in the deterioration of transit agencies' financial sustainability. Highlights: Examine impact of productivity, labor union, and contracting out on cost escalation. Estimate random effect model on a 17-year and 415-bus transit agency panel. Transit unit cost increase is far worse than what Baumol's cost disease predicts. Contracting out reduces unit costs, and lower wages only explain part of the effect. Unique transit labor law is a likely driver of the unit cost growth above inflation.